Pengaruh Kualitas Pelayanan, Fasilitas, Lokasi, dan Harga Terhadap Kepuasan Konsumen Apartemen Green Bay di Jakarta Utara - Mimi SA; Sanny Ekawati (STAI Asy-Syukriyyah, 2016)
The purpose of this study was to analyze the influence of the quality of service, facilities, location, and price to customer satisfaction of Green Bay Apartment in North Jakarta. Method of data collection was done by distributing questionnaires to 94 respondents. Sampling technique using Simple Random Sampling. The results showed that the quality of service, facilities, location, and prices has significant effect on customer satisfaction with the level of probability of 90%.